2020
DOI: 10.1075/jslp.20009.nag
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the scope of L2 intelligibility research

Abstract: Abstract This study investigated relationships among intelligibility, comprehensibility, and accentedness in the speech of L2 learners of Spanish who completed a prompted response speaking task. Thirty native Spanish listeners from Spain were recruited through Amazon Mechanical Turk to transcribe and rate extracted utterances, which were also coded for grammatical and phonemic errors, and speaking rate.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 29 publications
(46 reference statements)
1
11
0
Order By: Relevance
“…As for rater fit statistics, a range of 0.50-1.50 for infit values can be interpreted as good internal consistency (Eckes, 2015), and all but one listener (infit = 2.08) was in that range. With respect to the rating categories, foreign accent was the most severely rated (logit value of 0.78), which is in line with previous research (e.g., Munro & Derwing, 1995;Nagle & Huensch, 2020), while comprehensibility and fluency yielded more lenient ratings (logit values of -0.57 and -0.21, respectively). According to Eckes (2015), rating scale effectiveness may also be examined through fit statistics such as the mean-square outfit statistic, which should not exceed 2.…”
Section: Rasch Modelssupporting
confidence: 89%
See 2 more Smart Citations
“…As for rater fit statistics, a range of 0.50-1.50 for infit values can be interpreted as good internal consistency (Eckes, 2015), and all but one listener (infit = 2.08) was in that range. With respect to the rating categories, foreign accent was the most severely rated (logit value of 0.78), which is in line with previous research (e.g., Munro & Derwing, 1995;Nagle & Huensch, 2020), while comprehensibility and fluency yielded more lenient ratings (logit values of -0.57 and -0.21, respectively). According to Eckes (2015), rating scale effectiveness may also be examined through fit statistics such as the mean-square outfit statistic, which should not exceed 2.…”
Section: Rasch Modelssupporting
confidence: 89%
“…These three constructs, while interrelated, capture distinct facets of oral communicative competence. For one, accented speech is often highly comprehensible (Munro & Derwing, 1995;Nagle & Huensch, 2020), and numerous studies have shown that different bundles of linguistic features predict comprehensibility and accentedness. For instance, Trofimovich and Isaacs (2012) found that rhythm (vowel reduction ratio) was the strongest predictor of accent, whereas type frequency was the strongest predictor of comprehensibility.…”
Section: Listener-based Ratings As a Window Into Oral Communicative Competencementioning
confidence: 99%
See 1 more Smart Citation
“…Although comprehensibility has typically been measured through 7-or 9-point Likert scales (e.g., Munro & Derwing, 1995), researchers have occasionally opted for continuous scales over ordinal ones, using a straight line bounded by endpoint descriptors in a paper-and-pencil format (e.g., Isaacs et al, 2015), as in this study, or a slider to record the rating in a computer or online interface (e.g., Saito et al, 2017). Existing scale validation and scale comparison work indicates that there is little difference in the ratings of comprehensibility obtained through scales of various lengths and resolutions (Isaacs & Thomson, 2013), through different scale types (Munro, 2018), or through static or dynamic assessments (Nagle et al, 2019), which implied that the choice of the comprehensibility scale in this study was unlikely to have impacted rating validity.…”
Section: Speaking Tasks and Target Ratingsmentioning
confidence: 99%
“…Listeners may both understand a speaker and find the speaker easy to understand or may understand a speaker while needing to expend considerable effort. This is the basis for the distinction between intelligibility, a measure of actual understanding, and comprehensibility, listeners' perceived ease of understanding (Munro & Derwing, 1995;Nagle & Huensch, 2020). While intelligibility is a sensible baseline, most L2 speakers want their speech to be easy to understand, a goal that is more closely aligned with the notion of comprehensibility.…”
Section: Introductionmentioning
confidence: 99%